The present perfect in the english used by L1 Chinese and L1 Malay language learners - Kwan, Lee Yin (2020)
It is widely acknowledged that the English present perfect is one of the more challenging grammatical constructions for learners of English as a second (ESL) or foreign language (EFL) to attain. According to Leech (2004), there are four main functions of the English present perfect, namely State-up-to-the Present (SP), Indefinite Past (IP), Habit-leading-to-the Present (HP) and Resultative Past (RP). SP indicates a state that extends over a period lasting up to the present moment; IP refers to some indefinite happening (or happenings) in the past that are “at-least-once-before-now”; HP highlights “a state consisting of repeated events”; and RP denotes the result of a past event that is still in operation at the present time. The Chinese and Malay languages do not have a tense system, which means there is no exact equivalent of the English present perfect in Chinese and Malay. Due to the complex nature by which the English present perfect functions, teachers of English as a second language in Malaysia have observed that the English present perfect is often an area of serious difficulty for their students in English grammar. Using the functional perspective governing the four functions of the English present perfect by Leech (2004), this thesis discusses the extent to which L1 Chinese and L1 Malay ESL learners in Malaysia know the full range of functions of the English present perfect and can use them in English production. The study also aims to find out the specific present perfect functions that the participants utilise the best and worst as well as the main factors determining the relative lack of success in the acquisition of the present perfect in relation to results obtained by L1 Chinese and L1 Malay participants of two proficiency levels. A total of 60 L1 Chinese learners and 60 L1 Malay learners whose proficiency in English was intermediate and advanced participated in this study based on their performance in the Oxford Placement Test 2 (OPT2) (Allan, 2004). The participants were Literature and Linguistics students of the Faculty of Modern Languages and Communication and medical students of the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. All were in the second to final year of their programmes. The instruments used consist of three elicitation tasks: a cloze task, a Grammaticality Judgement Task and a translation task. The data obtained from the three tasks were analysed quantitatively using the Statistical Package for Social Sciences (SPSS) version 25 programme with respect to descriptive statistics to obtain frequency counts and percentage. Comparison was made between the mean differences and the significant differences between the participants of the two language groups at the two levels of proficiency using t-tests. For multiple comparisons, Tukey’s Post Hoc Test was also conducted. The data was analysed qualitatively i.e. the percentages of errors made in the use of the four functions of the present perfect were analysed and explained by identifying the differences between the participants’ mother tongue and the target language and considering the participants’ tendency to use certain verb forms in various situations. The results of the study showed that the L1 Chinese and L1 Malay learners have not fully integrated the four principal meanings conveyed by the English present perfect form in a native-like way. Data collected attest to the fact that both groups of participants performed best in the use of the state-up-to-the present function of the present perfect and worst in the use of the habit- leading-to-the present function. The participants also tended to use the simple past verb form instead of the present perfect verb form in present perfect environments in spite of contextual markers that signalled the use of the present perfect. The persistent difficulty in correctly using the present perfect can be linked to interacting factors such as markedness, there being no equivalent form to express the English present perfect in Chinese and Malay and the complexity in meaning and ambiguous nature of the English present perfect itself. The study highlights the importance of investigating the acquisition of the English Present Perfect by L2 learners and provides some pedagogical perspectives for L2 English instructors. Based on the findings, the researcher formulated important recommendations for language instructors to improve pedagogical language approaches to facilitate language learners in acquiring ease of use of the English present perfect.